Textured nanoporous Mo:BiVO4 photoanodes with high charge transport and charge transfer quantum efficiencies for oxygen evolution. Issue 4 (11th February 2016) - Nair, Vineet; Perkins, Craig L.; Lin, Qiyin; Law, Matt
Abstract : Nanoporous, catalyst-free BiVO4 films made by a simple spin coating process show a hole-limited charge transport quantum efficiency of ∼70% and >60% charge transfer efficiency for oxidizing water. Abstract : We have developed a simple spin coating method to make high-quality nanoporous photoelectrodes of monoclinic BiVO4 and studied the ability of these electrodes to transport photogenerated carriers to oxidize sulfite and water. Samples containing molybdenum and featuring [001] out-of-plane crystallographic texture show a photocurrent and external quantum efficiency (EQE) for sulfite oxidation as high as 3.1 mA cm −2 and 60%, respectively, at 1.23 V versus reversible hydrogen electrode. By using an optical model of the electrode stack to accurately determine the fraction of electrode absorptance due to the BiVO4 active layer, we estimate that on average 70 ± 5% of all photogenerated carriers escape recombination. A comparison of internal quantum efficiency as a function of film processing, illumination direction, and film thickness shows that electron transport is efficient and hole transport limits the photocurrent (hole diffusion length <40 nm). We find that Mo addition primarily improves electron transport and texturing mostly improves hole transport. Mo enhances electron transport by thinning the surface depletion layer or passivating traps and recombination centers at grain boundaries and interfaces, while improved hole transport in textured films may result from more efficient lateral hole extraction due to the texturing itself or the reduced density of deep gap states observed in photoemission measurements. Photoemission data also reveal that the films have bismuth-rich, vanadium- and oxygen-deficient surface layers, while ion scattering spectroscopy indicates a Bi–V–O surface termination. Without added catalysts, the plain BiVO4 electrodes oxidized water with an initial photocurrent and peak EQE of 1.7 mA cm −2 and 30%, respectively, which equates to a hole transfer efficiency to water of >64% at 1.23 V. The electrodes quickly photocorrode during water oxidation but show good stability during sulfite oxidation and indefinite stability in the dark. By improving the hole transport efficiency and coating these nanoporous BiVO4 films with an appropriate protective layer and oxygen evolution catalyst, it should be possible to achieve highly efficient and stable water oxidation at a practical pH.